Potrzeby informacyjne w procesie zarządzania ryzykiem przedsiębiorstwa - Jaworska Elżbieta; Łagodzki Przemysław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The issue of risk is directly related to running a business activity. Thus, it seems important to define and determine the information requirement regarding the risk of activity of enterprise and the manners of its limitation. The article presents questions concerning the essence of enterprise activity risk and its classification. Furthermore, the authors make the identification and classification of information needs about risk management for its limitation of interaction of a negative result on running an enterprise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 103-112